The effect of suppression agents towards liquefied petroleum gas(LPG)& natural gas(NG)explosion limit - Julius, Raymondee Junior (2010)
The objective of the research is to determine the effect of suppression agents towards liquefied petroleum gas(LPG)and natural gas(NG)explosion limit.The main target of the research is to identify the best suppression agents that can be used in the suppression system to mitigate explosion from its early stage thus preventing catastrophic.In the experiment,several types of suppression agents are used which are ammonium phosphate,argon gas and carbon dioxide gas.Liquefied petroleum gas(LPG)and natural gas(NG)is used as a fuel source.The purpose of using LPG as the fuel source is because LPG is one of the most dangerous sources of fuels that can easily involve in an explosion due to its properties that can cause boiling liquid expanding vapour explosion (BLEVE).Since natural gas is also commonly used in the industries and as well as residential area,it is best to make sure that the prevention is fully secure.the lower the maximum pressure,the more effective the suppressants are. The experiments are carried out by using the gas fire explosion unit.Conventional suppression agent that is commonly used in the industries nowadays is carbon dioxide. However,carbon dioxide can give a side effect to the environment.Therefore by the end of the experiments,the results will show that ammonium phosphate does mitigate the gas explosion more effectively thus overcoming the problem cause by the conventional suppression agent.